Effects of Emblica Extract (Phyllanthus emblica) on Color and Antimicrobial Quality of Avocado Puree During Freezing Storage - Suwannate, Ploypailin; Issara, Utthapon; Wannasawad, Kittikoon; Chotiko, Arranee (Journal of Food Health and Bioenvironmental Science, 2023)
Emblica (Phyllanthus emblica) fruits have both antioxidant and antimicrobial activities as well as enzyme-inhibiting properties. They contain high levels of ascorbic acid and citric acid, preventing the browning reaction in minimally proceeded fruits and vegetables. This research investigated the effect of emblica fruit extract on the quality of avocado puree during freezing storage. Emblica fruits were ethanolic extracted and used as anti-browning and anti-microbial agents. Ripe avocados were selected and blanched in carbonate buffer (pH 10.6). Acidulants, including ascorbic acid and emblica fruit extract, were then added prior to blending to become homogenous. The puree was packed and stored at -20°C for 4 weeks. During storage, the puree was determined for their color, pH and total bacterial plate counts. The result showed that the emblica fruit extract had antioxidants activity and could inhibit Staphylococcus pasteuri, spoilage bacteria isolated from avocado puree. The emblica fruit extract could delay the browning reaction during storage. However, the extract concentration had an influence on the puree color, causing the puree lightness to decrease. Blanching helped destroyed some contaminated bacteria in the avocado. After storage at -20°C for 4 weeks, less than 1 log CFU/g were detected in all avocado puree treatments, which were blanched. This study indicates that the emblica fruit extract could be used as an acidulant to prevent the blanched avocado from the browning reaction.